Implementation of Communicative Language Teaching (CLT) in Improving the Speaking Skills of English Language Education Students: A Literature Review - Destiani, Nadia (Maliki Interdisciplinary Journal, 2026)
A B S T R A C T Speaking skill holds a pivotal role as one of the most essential yet demanding language competencies for English Education (Tadris Bahasa Inggris) students who are being trined as future EFL teachers. The Communicative Language Teaching (CLT) approach has been widely acknowledged as an effective pedagogical method to foster learners’ communicative competence. This study systematically reviews the implementation of CLT in enhancing the speaking abilities of English Education students. Data were gathered from diverse academic sources, including journals, dissertations, and research reports housed in the repository of UIN Maulana Malik Ibrahim Malang, along with other relevant references. The findings indicate that CLT substantially improves students’ confidence, fluency, and communicative competence through authentic and interactive learning activities. Moreover, CLT promotes consistent use of the target language in real-life contexts and nurtures a collaborative classroom environment. The pedagogical implications highlight the necessity of systematically embedding CLT principles into the English Education curriculum, particularly within speaking courses, to prepare prospective teachers who are both competent and communicative.